2022
DOI: 10.1111/jch.14490
|View full text |Cite
|
Sign up to set email alerts
|

Immediate post‐exercise blood pressure and arterial stiffness in hypertensive and normotensive older females

Abstract: Although it has been suggested that increased arterial stiffness is linked to exaggerated blood pressure (BP) from brief moderate exercise, it is not clear whether this occurs in older adults with and without hypertension. This study investigates whether the immediate post‐exercise systolic BP following brief moderate exercise is associated with arterial stiffness in older females with different BP status. This cross‐sectional study included 191 older females aged 60–80 years without known cardiovascular disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The major findings of this study were as follows: (Costa et al, 2022) the post‐exercise BP response was greater in older normotensive and SBP‐controlled hypertensive than in SBP‐uncontrolled hypertensive females; (Costa et al, 2020) MVC and muscle thickness were not associated with the change in BP from pre‐ to post‐exercise in older females; (Millar et al, 2009) muscle echo intensity was negatively correlated with the change in DBP from pre‐ to post‐exercise in older normotensive females only. Further, exploratory analysis suggested that the increase in DBP from pre‐ to post‐exercise was smaller in older normotensive females with greater muscle echo intensity than in those with lower echo intensity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The major findings of this study were as follows: (Costa et al, 2022) the post‐exercise BP response was greater in older normotensive and SBP‐controlled hypertensive than in SBP‐uncontrolled hypertensive females; (Costa et al, 2020) MVC and muscle thickness were not associated with the change in BP from pre‐ to post‐exercise in older females; (Millar et al, 2009) muscle echo intensity was negatively correlated with the change in DBP from pre‐ to post‐exercise in older normotensive females only. Further, exploratory analysis suggested that the increase in DBP from pre‐ to post‐exercise was smaller in older normotensive females with greater muscle echo intensity than in those with lower echo intensity.…”
Section: Discussionmentioning
confidence: 58%
“…Exaggerated post‐exercise blood pressure (BP) is associated with cardiovascular disease risk factors, such as higher arterial stiffness (Costa et al, 2022) and reduced arterial compliance (Costa et al, 2020) in older hypertensive and normotensive females. On the other hand, post‐exercise hypotension after resistance exercise also occurs in older females as well as males (Millar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that CAD patients likely benefit from dynamic exercise peripherally from lower body exercise. Blood pressure may be related to different BP and health status, for these (Costa et al, 2022) in cross-sectional research investigated whether the immediate post-exercise systolic BP following brief moderate exercise is associated with arterial stiffness in older females with different BP statuses. This cross-sectional study included 191 older females aged 60-80 years without known cardiovascular disease (CVD).…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent study showed that higher systolic blood pressure after exercise in older women with different blood pressure levels was linked to stiffer arteries. 32 The brachial-ankle pulse wave velocity (PWV) was used to measure the arterial stiffness index in 92 men (aged 42±9 years) without a history of cardiovascular disease or stroke. Regression analysis revealed a signi cant correlation between HRE and PWV.…”
Section: Studies Comparing Arterial Stiffness and Hypertensive Respon...mentioning
confidence: 99%